Core muscle activation and activity throughout the different phases of the golf swing: A literature review - Loock, H. V.; Grace, J. M.; Semple, S. J. (Strength and Conditioning Journal, 2013)
The golf swing requires specific muscle contraction. The purpose of this study is to compile a structured literature review of core muscle activity within different phases of the golf swing. A literature search was conducted to capture all articles applicable. A descriptive analysis was undertaken. The search resulted in 150 articles, 59 of which met inclusion criteria; 16 were concerned with core muscles within different phases of the golf swing. Available research is limited to specific muscle groups and only addresses certain phases of the golf swing. No data portrays the activity of core muscles during different phases of the golf swing.